Fascist Ideology and the Conceptual Approach : The Conceptual Configuration of Fascist Leaders - Martins, Carlos (2022)
Taking fascist ideology seriously, our study uses a conceptual approach to analyze the ideology of fascist leaders. We thus argue that fascist ideology can be approach like any other ideology and that the leaders can be an interesting source of information about this topic. This conceptual approach can grasp both the main features of a generic fascist ideology as well as some of the most important permutations. Focusing on the interlinkages between concepts, we untangled a configuration for generic fascism: Nation, State, Corporatism, Revolution, Authority, Violence and Empire. After this, we were able to analyze the ideological content of seven different fascist leaders, highlighting the different possible interactions between core concepts and adjacent concepts. We were thus able to identify the recurrent patterns of conceptual interlinkages that fascist leaders could use to structure the ideology of their movement.